AVRUPA BİRLİĞİ YURTTAŞLIĞI AVRUPA KİMLİĞİ SORUNUNA ÇÖZÜM OLUŞTURABİLİR Mİ? - Yeşim Gündoğdu (Ankara Avrupa Çalışmaları Dergisi)
European Union citizenship was firstly established within the Maastricht Treaty.As European Union (EU) has been a project that is created by the European elites, the Union has a democratic legitimacy problem since the foundation of the European Communities. Therefore EU citizenship is seen as a key concept to solve the gap between the EU institutions and the individuals. In this paper I am going to discuss the applicability of current EU citizenship status to democratic legitimacy problem of the Union. At the beginning o f the paper I am going to give a short history of the development of different citizenship traditions in Europe. Then I will discuss the legal content o f the Union citizenship and focus on the scope o f the rights recognized in the Maastricht Treaty. At the end I am going to focus on the relationship of Union citizenship and a common European identity. As the result of the paper, I am going to assert following statements: Union citizenship problem cannot be distinguished from a common European identity problem. Like a common European identity problem, the definition o f the Union citizenship has not been completed yet and the content o f the Union citizenship will be defined with the framework of a common European identity.